Revolution in Bavaria, 1918-1919 the Eisner regime and the Soviet Republic. - Mitchell, Allan, 1933- (Princeton legacy library., 1965)
The tangled affairs in Bavaria at the close of World War I constitute a unique and important part of the early Weimar Republic. This study of the 1918 revolution, based on archival sources such as cabinet protocols and bureaucratic records, traces in detail the overthrow of the Wittelsbach dynasty and the foundation of the Bavarian Republic under Kurt Eisner. It also broadens and balances current understanding of the first Communist attempts to penetrate the heartland of Europe. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.